2017
DOI: 10.3892/mco.2017.1200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of xerostomia and its impact on quality of life in head and neck cancer patients undergoing radiation therapy

Abstract: Abstract. Xerostomia in head and neck (H&N) cancer patients significantly affects their quality of life (QoL). The aim of the present study was to investigate the associations among QoL, xerostomia and quantity of saliva in a sample of H&N cancer patients who had received conventional radiotherapy (RT). A total of 60 H&N adult patients were enrolled in this prospective study. The patients completed the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (QLQ-C30), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
3
12
0
1
Order By: Relevance
“…A significant correlation between salivary flow rate and xerostomia complaints was not found in our study, as agrees with others (25,29). Moreover, although xerostomia could have a significant effect on the quality of life (30), this potential effect might be underestimated, since in most studies questions regarding the presence of oral complaints were nonspecific. Studies on DTC patients that explicitly asked for xerostomia complaints reported a higher prevalence of these complaints than generally assumed by physicians (31).…”
Section: Discussionsupporting
confidence: 86%
“…A significant correlation between salivary flow rate and xerostomia complaints was not found in our study, as agrees with others (25,29). Moreover, although xerostomia could have a significant effect on the quality of life (30), this potential effect might be underestimated, since in most studies questions regarding the presence of oral complaints were nonspecific. Studies on DTC patients that explicitly asked for xerostomia complaints reported a higher prevalence of these complaints than generally assumed by physicians (31).…”
Section: Discussionsupporting
confidence: 86%
“…It is estimated that at least 1-year of follow-up is required to determine the effect of RT on xerostomia [32]. Thus, the follow-up period in our present study may be considered as sufficient to provide adequate information in terms of xerostomia following RT.…”
Section: Discussionmentioning
confidence: 92%
“…9 Another different results observed in USA study conducted in 2006, as the primary tumor sites was in the oropharynx as (68%). 10 An agreement observed in study conducted in Greece (2017) included 60 patients, where half of them had laryngeal/hypopharyngeal cancer (28% and 2% respectively). 11 About half of patients (49%) received radiotherapy ≥70 GY, and concerning the chemotherapy (90%) of the patients didn't take chemotherapy, only 68% previously received chemotherapy.…”
Section: Discussionmentioning
confidence: 60%
“…Out of 63 Iranian patients participated in a study conducted in 2012, 43 patients (77.8%) were male with male: female ratio was 3.5:1. 10 Finally, higher results observed in Greece in a study conducted on 60 patients with head and neck cancer, as male represented 80% of them (48 patients) with male: female ratio was 4:1. 11…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation